If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 8 + 2(4x + -2) + 2(8x + 21 + -1(6x + 5)) = 180 Reorder the terms: 6x + 8 + 2(-2 + 4x) + 2(8x + 21 + -1(6x + 5)) = 180 6x + 8 + (-2 * 2 + 4x * 2) + 2(8x + 21 + -1(6x + 5)) = 180 6x + 8 + (-4 + 8x) + 2(8x + 21 + -1(6x + 5)) = 180 Reorder the terms: 6x + 8 + -4 + 8x + 2(8x + 21 + -1(5 + 6x)) = 180 6x + 8 + -4 + 8x + 2(8x + 21 + (5 * -1 + 6x * -1)) = 180 6x + 8 + -4 + 8x + 2(8x + 21 + (-5 + -6x)) = 180 Reorder the terms: 6x + 8 + -4 + 8x + 2(21 + -5 + 8x + -6x) = 180 Combine like terms: 21 + -5 = 16 6x + 8 + -4 + 8x + 2(16 + 8x + -6x) = 180 Combine like terms: 8x + -6x = 2x 6x + 8 + -4 + 8x + 2(16 + 2x) = 180 6x + 8 + -4 + 8x + (16 * 2 + 2x * 2) = 180 6x + 8 + -4 + 8x + (32 + 4x) = 180 Reorder the terms: 8 + -4 + 32 + 6x + 8x + 4x = 180 Combine like terms: 8 + -4 = 4 4 + 32 + 6x + 8x + 4x = 180 Combine like terms: 4 + 32 = 36 36 + 6x + 8x + 4x = 180 Combine like terms: 6x + 8x = 14x 36 + 14x + 4x = 180 Combine like terms: 14x + 4x = 18x 36 + 18x = 180 Solving 36 + 18x = 180 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-36' to each side of the equation. 36 + -36 + 18x = 180 + -36 Combine like terms: 36 + -36 = 0 0 + 18x = 180 + -36 18x = 180 + -36 Combine like terms: 180 + -36 = 144 18x = 144 Divide each side by '18'. x = 8 Simplifying x = 8
| 1/7(3x-2)=X/5+10/5 | | y+3/8=y-9/7 | | -4k-8=24 | | -1+2x=1x+3 | | 5y=70 | | 7(5-x)=3(3(x+1)) | | (5/4)+2 | | 4(3y-5)=4y-60 | | 3u/7=-12 | | (-3/8)/(13/4) | | 5/3x+9=21 | | r+9=48 | | 41/4+567/8 | | -2+7(2z+1)=-7(-7z-2)-7 | | 5/7/7/10= | | 3x+7+2(4x-5)=25-3x | | (5/8)-1 | | 4u+36=-12u+18+6u | | 6+k/4=-8 | | T/7+3=-2 | | 4/3-3/3 | | 35+7y/7 | | 4m-(2+3m)=19 | | 24=-7+3y | | 3v=15 | | 2=4/5x-2x+8 | | -23+p=-38 | | 3x(x+2)-4(x+2)=0 | | 4/3x-x | | 9u^2+42u+49=0 | | 5/x=-x+4 | | 5t^2+8T-48=0 |